MYSTERIES ZALISCOI OF MOUNTAIN: BECOMING OF MARK CHEREMSHINA AS CREATIVE PERSONALITY - Pihmanets, R. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
In the article there is speech about those factors which directly affected forming of creative personality of Mark Cheremshina. Among them the attention is accented on mastering of experience „starovicou", influencing of aesthetically beautiful priorities of George Fed’covich, and also on the acquaintance with achievements of the modern European writing. Traced the first steps of Mark Cheremshina as a writer, searches by him the artistic voice.